Biogenic isoprene emissions, dry deposition velocity, and surface ozone concentration during summer droughts, heatwaves, and normal conditions in southwestern Europe - Guion, Antoine; Turquety, Solène; Cholakian, Arineh; Polcher, Jan; Ehret, Antoine; Lathière, Juliette (Atmospheric chemistry and physics, 2023)
At high concentrations, tropospheric ozone (O3) deteriorates air quality, inducing adverse effects on human and ecosystem health. Meteorological conditions are key to understanding the variability in O3 concentration, especially during extreme weather events. In addition to modifying photochemistry and atmospheric transport, droughts and heatwaves affect the state of vegetation and thus the biosphere–troposphere interactions that control atmospheric chemistry, namely biogenic emissions of precursors and gas dry deposition. A major source of uncertainty and inaccuracy in the simulation of surface O3 during droughts and heatwaves is the poor representation of such interactions. This publication aims at quantifying the isolated and combined impacts of both extremes on biogenic isoprene (C5H8) emissions, O3 dry deposition, and surface O3 in southwestern Europe. First, the sensitivity of biogenic C5H8 emissions, O3 dry deposition, and surface O3 to two specific effects of droughts, the decrease in soil moisture and in biomass, is analysed for the extremely dry summer 2012 using the biogenic emission model MEGANv2.1 and the chemistry transport model CHIMEREv2020r1. Despite a significant decrease in biogenic C5H8 emissions and O3 dry deposition velocity, characterized by a large spatial variability, the combined effect on surface O3 concentration remains limited (between +0.5 % and +3 % over the continent). The variations in simulated biogenic C5H8 emissions, O3 dry deposition, and surface O3 during the heatwaves and agricultural droughts are then analysed for summer 2012 (warm and dry), 2013 (warm), and 2014 (relatively wet and cool). We compare the results with large observational data sets, namely O3 concentrations from Air Quality (AQ) e-Reporting (2000–2016) and total columns of formaldehyde (HCHO, which is used as a proxy for biogenic emissions of volatile organic compounds) from the Ozone Monitoring Instrument (OMI) of the Aura satellite (2005–2016). Based on a cluster approach using the percentile limit anomalies indicator, we find that C5H8 emissions increase by +33 % during heatwaves compared to normal conditions, do not vary significantly during all droughts (either accompanied or not by a heatwave), and decrease by −16 % during isolated droughts. OMI data confirm an average increase in HCHO during heatwaves (between +15 % and +31 % depending on the product used) and decrease in HCHO (between −2 % and −6 %) during isolated droughts over the 2005–2016 summers. Simulated O3 dry deposition velocity decreases by −25 % during heatwaves and −35 % during all droughts. Simulated O3 concentrations increase by +7 % during heatwaves and by +3 % during all droughts. Compared to observations, CHIMERE tends to underestimate the daily maximum O3. However, similar sensitivity to droughts and heatwaves are obtained. The analysis of the AQ e-Reporting data set shows an average increase of +14 % during heatwaves and +7 % during all droughts over the 2000–2016 summers (for an average daily concentration value of 69 µg m−3 under normal conditions). This suggests that identifying the presence of combined heatwaves is fundamental to the study of droughts on surface–atmosphere interactions and O3 concentration.